The role of p62 in the crosstalk between AMPK and NRF2 induced by metabolic stress in the tumor microenvironment and its implications for the development of anticancer strategies - 최은지 (The Graduate School, Ajou University, 2024)
In the context of nutrient deficiency and toxic accumulation, which are characteristics of the tumor microenvironment, tumor cells have efficient adaptation strategies to metabolic stress for survival. In LKB1-mutant NSCLC, co-occurring mutations in KEAP1 activate NRF2 to compensate for the loss of LKB1-AMPK activity during metabolic adaptation. Here, we found that metabolic stress increases the expression and phosphorylation of p62, which is essential for the activation of the LKB1-AMPK pathway and NRF2, a regulator of antioxidant gene expression, thereby enhancing antioxidant defense and tumor growth. Activation of AMPK and NRF2 by p62 induces autophagic degradation of KEAP1 and formation of AXIN- LKB1-AMPK complexes in the lysosomal membrane, respectively. In addition, AMPK activation is required for the expression and phosphorylation of p62 induced by metabolic stress, confirming the existence of a double positive feedback loop between AMPK and p62. AMPK, which is activated by metabolic stress, increases the expression of p62 by dephosphorylation of TFE3/TFEB in a PP2A-dependent manner, and activates NRF2 through KEAP1 degradation. Furthermore, p62 phosphorylation was increased through TAK1 activated by ROS and lysosomal calcium secretion. Importantly, S24 and S226 phosphorylation of p62 are essential for AMPK and NRF2 activation. Taken together, our results demonstrate a novel double positive feedback loop between AMPK and p62, which leads to the simultaneous activation of AMPK and NRF2. AMPK; p62(SQSTM1); NRF2; Lysosome Biogenesis; NSCLC
학위논문(박사)--약학과,2024. 8
Keywords: AMPK; AXIN; Lysosome. NSCLC; NRF2; p62